Pendekatan Dakwah al-Wasatiyyah Syeikh Abdul Rauf Ali al-Fansuri (m.1693): Moderate Da’wah Approach by Syeikh Abdul Rauf Ali al-Fansuri (d.1693) - Aini, Zulkefli; Sa’ari, Che Zarrina; Abdul Ghani, Mohamad Zulkifli (Afkar: Jurnal Akidah dan Pemikiran Islam, 2018)
The arrival of Islam into the Malay world places the position of preachers in the da`wah field in the region. The missionaries of Islam came with the orientation and images of preachers and Sufi scholars who master the various disciplines include the knowledge of tasawuf. However, conflicts arose among them from the point of understanding and interpretation of the knowledge of sufism especially involving sunni sufism and falsafi sufism. During such a fuss, Syeikh Abdul Rauf Ali al-Fansuri appeared with his da`wah efforts to reconcile the two streams through wasaṭiyyah approach. In this regard, this article is presented to identify the approach of preaching that was used by Sheikh Abdul Rauf Ali al-Fansuri when faced with problems in society such as issues arising from the conflict of clerical heritage and past preachers such as Hamzah Fansuri, Syamsuddin al-Sumatra’i and Nur al-Din al-Raniri and issues related to monarchy at that time. The methodology used in this study is in qualitative. The data are analyzed descriptively according to the theme and the concept of wasaṭiyyah preaching. The findings show that Syeikh Abdul Rauf used al-ḥikmah approach in the framework of wasaṭiyyah al-Islām by prioritize “something more important than the important” (taqdīm al-aham `alā al-muhim) to solve the problems faced at that moment. This is important for preachers who want to preach in the framework of community-mindedness and incorporate basic knowledge in Islamic teachings with the knowledge of al-thaqāfah al-wāqi`iyyah.